Critical Theory as a foundation for Pragmatic Information Systems Design - Gerald Benoît (Information Research: An International Electronic Journal)
This paper considers how designers of information systems and end-user perspectives, communication models and linguistic behaviors differ. A critique of these differences is made by applying Habermas's communicative action principles. An empirical study of human-human information seeking, based on those principles, indicates which behaviors are predictors of successful interactions and so are candidate behaviors may be integrated into computerized information systems.